NURSING CARE TO CLIENTS WITH FOCUS STUDY OF CHANGES IN SCHIZOPHRENIA SENSORY PERCEPTION OF AUDITORY HALLUCINATION CASE STUDY IN RSJ PROF. DR. SOEROJO MAGELANG - Novitri Andalusia (Universitas Muhammadiyah Kudus, 2017)
Background: Mental disorder that is one of the major in developing countries is schizophrenia.Based on the data of Basic Health Research (RISKESDAS, 2013) and combined with data from Pusdatin Kemenkes, the prevalence of mental disorders in Central Java was 0.23% for the age of 15 years and above the population of 24,089,433 people. Objective: describe the management of nursing care Schizophrenia with focus of study of Sensory Perception in Auditory Hallucinations. Method: The method used in this research is descriptive method by using approach of nursing process. Subjects in this study were Schizophrenic clients with sensory auditory sensory perception changes of 2 clients. Results: The provision of nursing care to clients of schizophrenia with a change in Sensory Perception Auditory Hallucinations showed different results on both clients after the provision of interventions in accordance with the client's verbal and nonverbal responses. Conclusion: The provision of nursing care to clients tailored to the client's response during nursing care.